The role of collaborative innovation networks in the relationship between firms' innovation capabilities and firm performance - Canbul, Aslihan; Cemberci, Murat (INDERSCIENCE ENTERPRISES LTD, 2024)
New product development is an expensive process involving high risk and is resource-intensive for companies. It is not always possible for companies to carry out this process in-house. Collaborative innovation networks are an important concept that will enable both practitioners and researchers to properly manage new product development. In the existing literature, the relationship between innovation capability and firm performance has been investigated, but no consistent studies have been found that shed light on the role played by suppliers, customers, competitors, and universities/research institutions in this relationship. The purpose of this research is to explore the impact of firms' innovation capability on firm performance through collaborative innovation networks. The research was carried out with 122 survey data of middle and senior managers working in technology companies operating in Turkey. The analysis shows that the cooperation of firms has a partial mediating effect on the relationship between innovation capabilities and firm performance.
Keywords: collaborative innovation networks; innovation capabilities; process innovation capability; product innovation capability; firm performance; Business & Economics